2013
DOI: 10.1094/phyto-08-12-0209-fi
|View full text |Cite
|
Sign up to set email alerts
|

The Endophytic Lifestyle of Escherichia coli O157:H7: Quantification and Internal Localization in Roots

Abstract: The foodborne pathogen Escherichia coli O157:H7 is increasingly associated with fresh produce (fruit and vegetables). Bacterial colonization of fresh produce plants can occur to high levels on the external tissue but bacteria have also been detected within plant tissue. However, questions remain about the extent of internalization, its molecular basis, and internal location of the bacteria. We have determined the extent of internalization of E. coli O157:H7 in live spinach and lettuce plants and used high-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 50 publications
3
68
1
3
Order By: Relevance
“…Both ECP variants from E. coli isolates Sakai and IHE3034 demonstrated enhanced adherence to spinach root polysaccharides compared with leaves, which supports previous findings of increased colonization in the roots (69). Furthermore, higher levels of ECP-mediated adherence of E. coli O157:H7 occurred in spinach compared with lettuce, which may be a result of the (49).…”
Section: Discussionsupporting
confidence: 84%
“…Both ECP variants from E. coli isolates Sakai and IHE3034 demonstrated enhanced adherence to spinach root polysaccharides compared with leaves, which supports previous findings of increased colonization in the roots (69). Furthermore, higher levels of ECP-mediated adherence of E. coli O157:H7 occurred in spinach compared with lettuce, which may be a result of the (49).…”
Section: Discussionsupporting
confidence: 84%
“…Once within the fruits, the pathogen can multiply to high densities (Gu et al 2011;Noel et al 2010). A recent study demonstrated that Escherichia coli can internally colonize both leaves and roots of lettuce and spinach (Wright et al 2013). Lastly, human norovirus and norovirus surrogates (Murine norovirus and Tulane virus) are also reported to colonize spinach stem and leaves (Hirneisen and Kniel 2013).…”
Section: Bacteriamentioning
confidence: 99%
“…Several studies have pointed to flies , arthropods, birds, wild mammals and reptiles (Wright et al, 2013) as other major sources of pathogen transmission. It has been shown that if fresh produce is grown near livestock, these vectors can easily carry faecal contaminants to plants (Doyle and Erickson, 2012;Fletcher et al, 2013;Wasala et al, 2013).…”
Section: Brotesmentioning
confidence: 99%
“…Thus, the environments in which food products are produced, processed and transported can all cause cross-contamination. Some of the most common sources of microbial contamination of fresh produce are related to contaminated irrigation water (Cooley et al, 2007;Wright et al, 2013) and the use of improperly treated or contaminated manure Olaimat and Holley, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation